Parental Perspectives Limit Disabled Children’s Future in Indonesia Higher Education - Putri, Nandita Alya; Gracia, Amanda Bunga (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
Ensuring equitable access to education for children with disabilities (CWD) is essential to maintaining their fundamental right to learning. Despite strides made in inclusive education, there remains a need for more cohesive efforts, as evidenced by a review in other research mentioning the lack of readiness and management. This research explores the factors influencing parents’ intentions regarding the pursuit of higher education for their disabled children, framed within the Theory of Reasoned Action (TRA) to explain the underlying behavioral drivers. The study indicates that parental attitudes play a significant role in shaping these intentions, with knowledge as a background factor, showing a moderate significance level. Emphasizing the pivotal role of cultivating positive attitudes towards inclusive higher education, the study underscores the critical importance of parental awareness regarding disability inclusion in higher education. Accordingly, efforts to strengthen parental understanding of inclusive education options are essential. The study advocates for collaborative actions between parents and educational institutions to establish nurturing and inclusive learning environments for disabled students. Its findings highlight the necessity for targeted interventions through communication strategy to enhance parental awareness and foster positive attitudes towards inclusive education, thus driving the accessibility and quality of education for CWD.